(3djhHGQOj (B:s (3CacGQ (B/s - (3CeGQLjs; (3GdeTGjNj, YHO GdefYe YKeGfs ((3CHh XHj (B:s (3gjFI CHh XHj ddKbGaI h GdJQGK, OGQ GdcJH GdhWfjI,s, 2010)
(3jUa GdTGYQ CeGQLj aj JYdjbg Ydi GdcJGH adSaI djhHGQOj HCfgG (B"(3JTGcld ehRGjjclqj ddQDjI hGdYGWaI, dG njYnOe cPdc Cf jJNnqddg NjlW ef GdHZV GdNGdU GdPj jHhM HGdeYGfGI GdTNUjI ddTGYQ(B." (3h jbhd aj ehVmY BNQ(B: "(3ZjQ Cnqf GdnqfhGI GdCUnd deVehf GdcKjQ ef GdCacGQ gj PGJgG aj LejY eG cJH djhHGQOj(B. (3GdSCe ef GdJHSjW hGdQJGHI hGdJcQGQ, hef GdaQGZ GdeJNnqdd aj GdhLhO, JQGLY Gdhge hSbhW GdJNjjd aj QDjI GdMjGI hGdEfSGf, GdGfJUGQ ddSMQ GdgpqT hGdNGFH ddTHGH(B..."s
Keywords: (3djhHGQOj, LGcheh,s -- 1798-1837; (3GdadSaI GdEjWGdjIs; (3GdadGSaI GdEjWGdjhfs -- (3JQGLes; Print books